Assessing The Interference of Mother Tongue Towards Students’ Spoken English Ability at SMPN 39 SBT - Armayanti Rumalutur; Karolis Anaktototy; Petrus Jacob Pattiasina (MATAI: International Journal of Language Education, 2021)
This research was conducted through descriptive qualitative research with the aim of the study are to find out kinds of phonological interference in the spoken English by students at SMPN 39 SBT and to describe factors which affecting the phonological interference in the spoken English by students at SMPN 39 SBT. The study taken a place in SMPN 39 SBT which located in desa Mida, Kec. Pulau Gorom. The subject of this study were eleven students of second grade at SMPN 39 SBT which spoken Bahasa Gorom as their mother tongue. The data were collected by using video recording, field not and interview. The researcher uses the content analysis which focuses on analyzing kinds of phonological interference by Uriel Weinrich, and the factors which affecting the phonological interference Rod Ellis. The result shown that there are 4 kinds of phonological interference found in the students’ utterances. Those are; 1). Under-differentiation of Phonemes. 2). Over-differentiation of Phonemes. 3). Reinterpretation of Distinction. 4). Actual Phone Substitution. The factors which include internal and external factors found in this study. They are; a). Motivation. b). Language Learners’ Attitude. c). Learners’ Personality. d). Teacher’s Behavior. e). Learning Environment.